1995
DOI: 10.1159/000288947
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Psychosomatic Disorders in ICD-10: Results of the Research Criteria Study

Abstract: The multicenter study with the research criteria in the field of psychotherapy/psychosomatic medicine considered nine cases. One patient with cardiac neurosis (F45.3) and one patient with a persistent somatoform pain disorder (F54.4) were diagnosed in category F45.x. The rater agreement was 63-68%. 54% of the correct diagnoses made for three cases of colitis ulcerosa and Crohn’s disease concurred (28%, 50%, and 80%). The case of anorexia nervosa (F50.0) was coded correctly by all of the raters, while the agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There are indications that presently a substantial number of dissociative disorder cases remains undiagnosed, and this may partly be due to a lack of recognition of somatoform dissociation. For example, Jantschek et al [37] found that only 50% of 129 diagnosticians at 13 psychiatric centers correctly assigned dissociative disorder. One can assume that in medical care many more cases will be missed.…”
Section: Discussionmentioning
confidence: 99%
“…There are indications that presently a substantial number of dissociative disorder cases remains undiagnosed, and this may partly be due to a lack of recognition of somatoform dissociation. For example, Jantschek et al [37] found that only 50% of 129 diagnosticians at 13 psychiatric centers correctly assigned dissociative disorder. One can assume that in medical care many more cases will be missed.…”
Section: Discussionmentioning
confidence: 99%
“…The ICD-10 research criteria study [3, 35] found rater agreement of 54% for the diagnosis ‘factitious disorder’. No data on interrater reliability have yet been published for direct, or overtly acted-out, autodestructive behaviour.…”
Section: Autodestructive Syndromes In the Established Classification mentioning
confidence: 99%
“…These psychological influences are perceived as mostly long-standing (worries, emotional conflicts, anticipation) and would not justify classification in another diagnostic category within ICD-10. chapter V [11).…”
Section: Discussionmentioning
confidence: 99%